Effect of Integrated Nutrient Management on Growth and Yield of Baby Corn (Zea mays L.) - Singh, Gurmeet; Singh, Navtej; Singh, Khushkaran (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted to study the effect of integrated nutrient management on growth, yield and quality of baby corn (Zea mays L.) on sandy loam soil during the kharif season of 2014. The experiment was laid down in randomized block design having seven treatments (Control, 100% recommended dose of nitrogen, 5 t of farm yard manure+100 kg inorganic nitrogen ha-1, 10 t of farm yard manure+75 kg inorganic nitrogen ha-1, 15 t of farm yard manure+50 kg inorganic nitrogen ha-1, 20 t of farm yard manure+25 Kg inorganic nitrogen ha-1, 25 t of farm yard manure ha-1 ) replicated four times. Significant increase in all growth characters, yield contributing characters, yield and fodder yield of baby corn was observed with integrated nutrient management over control. Moreover, among nutrient management treatments, the integration of 5 t of farm yard manure with 100 kg of inorganic nitrogen ha-1 came out to be best for all growth characters viz. plant height, leaf area index. The results obtained with application of 5 t of farm yard manure+100 kg inorganic nitrogen were comparable with recommended dose of nitrogen. Similarly, a significant increase in yield contributing characters, yield and fodder yield were observed with application of 5 t of farm yard manure+100 kg inorganic nitrogen ha-1, which is also found to be at par with the recommended dose of nitrogen (125 kg ha-1). Further, the above said treatment also gave maximum profit.